PENGEMBANGAN MEDIA CULTURE SMART BOX BERBASIS GAMIFIKASI TABUDI UNTUK MENINGKATKAN KEMAMPUAN KOLABORASI SISWA - Nuril Afidah; Cindya Alfi; Ragil Tri Oktaviani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Science and social science learning on Indonesian cultural material in elementary schools is often faced with a lack of concrete learning media, resulting in low student participation and collaboration skills. This study aims to develop and test the validity, feasibility, and effectiveness of Culture Smart Box media based on TABUDI gamification in improving the collaboration skills of fourth-grade students at SDI Ma’arif Tawangsari Garum, Blitar Regency. This research and development study applies the ADDIE model, comprising analysis, design, development, implementation, and evaluation stages. Data were collected using observation, interviews, and student collaboration questionnaires, which were analyzed qualitative-descriptively and quantitatively using the N-Gain test. The validation results by material experts reached 90% categorized as